ANALISIS DUGAAN PRAKTEK JUAL RUGI PRODUK IMPOR MELALUI SITUS E-COMMERCE SHOPEE - Suci Rahayu, Adinda; Suherman, Suherman (Universitas Ekasakti, 2022)
Technology that is increasingly developing brings about a variety of changes in people's lives, one of which is in the trade sector. The changes in the trade sector have been marked by the advent of e-commerce, which has greatly benefited the community in terms of facilitating buying and selling transactions. Unfortunately, this change has also created some problems related to business competition, such as the alleged of predatory pricing by imported products on the e-commerce site Shopee, as described in Article 20 No. 5 of 1999 regarding Prohibition of Monopoly and Unfair Bussiness Practices. The purpose of this study is to determine the truth behind the phenomenon of selling-buying practices and how the measures taken by the Komisi Pengawas Persaingan Usaha (KPPU). Since this is a qualitative study using the normative jurisprudential method, the sources used come from both library data and primary, secondary, and tertiary legal materials. The results of this study state that foreign businesses selling inexpensive imported goods on the e-commerce site Shopee do not practice deficit selling. Despite the prices of the imported products listed are cheaper than the local products, but there are factors that basically affect those prices. In addition, this approach does not satisfy the monopoly factor. Moreover, the first action was taken by the KPPU was to discuss the matter with the government, which has prepared several steps for the future.